CIPP Model for program evaluation at madrasah tsanawiyah - Syifaul Ummah; Ardi Ariyanto (Universitas Sarjanawiyata Tamansiswa, 2019)
The focus of the study is to investigate: (1) how the context of the excellent class program of MTs MINAT Kesugihan contributes to the success of the program, (2) how the input of the excellent class program of MTs MINAT Kesugihan contributes to the success of the program, (3) how the process of the excellent class program of MTs MINAT Kesugihan contributes to the success of the program, (4) how the product of the excellent class (EC) Program of MTs MINAT Kesugihan contributes to the success of the program. The research method was a qualitative research design. The objects of this study were: the headmaster of MTs MINAT, the director of the excellent class program, the excellent class teachers, and the excellent class students. The data were obtained from interview, classroom observation, and document analysis. Those data were analyzed by using Context, Input, Process, Product (CIPP) Model by Kellaghan and Stufflebeam (2003). The findings revealed some facts. First, in the context evaluation, it can be concluded that the goal, vision, and missions of the EC Program are relevant and formulated in order to meet the students’ needs. Second, in term of input evaluation, the teacher did not fulfill the requirements of a qualified teacher yet. Therefore, it influenced the teaching learning process in which they could not teach effectively. Finally, it affected the product which has not been successful in achieving the minimum score in the National Exam for English. Thus, the researcher suggested the school to conduct a workshop or training for the teachers so that the teachers’ teaching skills would improve. As the consequence, the students’ achievement would be better too.